Reference values for heart rate variability in older adults: A systematic review - Rocha, Alaine Souza Lima; Siqueira, Vitória de Barros; Maduro, Paula Andreatta; Batista, Laísla da Silva Paixão; Schwingel, Paulo Adriano (Psychophysiology, 2024)
Heart rate variability (HRV) is an early marker of risk for various health conditions, and its analysis serves as a valuable tool for assessing older adults. This study aimed to describe the reference values of HRV parameters in older adults through a systematic review of the literature. The review included searches in MEDLINE (via PubMed®), EMBASE, Latin American and Caribbean Health Literature, Scopus, and Web of Science (WOS). Studies presenting reference values for at least one HRV linear analysis measure in older adults were considered eligible. Out of 1618 studies identified, only 11 met the inclusion criteria. Sample sizes of older adults ranged from 21 to 6250 subjects. The HRV measures assessed (mean RR intervals, SDNN, RMSSD, PNN50, LF, HF, and LF/HF ratio) varied significantly between studies, with no standardized methods for HRV analysis. We concluded that reference values for HRV measures in older adults vary widely between studies. The scientific literature on HRV reference values in older adults is still limited, and future studies should standardize assessment methods for HRV measures in this population. This is first study aimed to describe the reference values of the heart rate variability (HRV) parameters specifically in older adults. Knowing the reference values of the HRV parameters in older adults is useful to tool provide data for HRV assessment and interpretation in this population and to include this tool in the routine healthcare of older adults. The intense commercial focus on wearables makes studies on this topic and its applicability even more relevant.